2008
DOI: 10.4314/ajhs.v15i1.30872
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of major HIV- risk related behaviour among SSS3 students in Port Harcourt Metropolis, Nigeria

Abstract: SUMMARYThe paper intended to find the prevalence of HIV infection risk-related behaviours among third year senior secondary school students in Port Harcourt metropolis. A cross-sectional survey among 1800 third year senior secondary school students randomly selected from thirteen secondary schools in Port Harcourt metropolis was done using two-stage sampling technique. Demographic data and information on the sexual behaviour of each student in the study group was obtained from self-administered structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…However, opinions are divided in Nigeria about secondary school students' level of awareness of HIV/AIDS and the sources of students' knowledge of the epidemic. While some scholars hold that the level of awareness of HIV/AIDS is high other scholars hold that the level of awareness of the epidemic is low among secondary school students (Aomreore, Alikor, & Nkanginieme, 2004;Wagbatsoma and Okojie, 2006;Sa'ad & Bello, 2006;Murtala, 2009;Adeleke et al, 2015;and Suleiman, 2018). Another set of scholars outside the academic environment of Nigeria argue that the students aged 15-19 years, single, belonging to the Muslim religion and studying at secondary schools were associated with poor knowledge on HIV/AIDS (Dzah, Tarkang & Lutala, 2019).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, opinions are divided in Nigeria about secondary school students' level of awareness of HIV/AIDS and the sources of students' knowledge of the epidemic. While some scholars hold that the level of awareness of HIV/AIDS is high other scholars hold that the level of awareness of the epidemic is low among secondary school students (Aomreore, Alikor, & Nkanginieme, 2004;Wagbatsoma and Okojie, 2006;Sa'ad & Bello, 2006;Murtala, 2009;Adeleke et al, 2015;and Suleiman, 2018). Another set of scholars outside the academic environment of Nigeria argue that the students aged 15-19 years, single, belonging to the Muslim religion and studying at secondary schools were associated with poor knowledge on HIV/AIDS (Dzah, Tarkang & Lutala, 2019).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The above four modes of transmission were identified by only 31%, 14.4%, 9.1% and 8%, respectively. Only 0.7% identified all the preventive measures (Aomreore, Alikor, & Nkanginieme, 2004). Another survey in western Nigeria assessing the level of awareness, knowledge and attitude towards HIV/AIDS among secondary school students in Atisbo Local Government Area, Nigeria, showed that participants possess relatively good knowledge of HIV/AIDS, reasonable knowledge of safe sexual practices and positive attitude towards sexuality, HIV/AIDS and people living with PLHIV (Adeleke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%